Bisphenol A exposure induces apoptosis and impairs early embryonic development in Xenopus laevis. (1st July 2021) - Ge, Yaming; Ren, Fei; Chen, Lingli; Hu, Dongfang; Wang, Xinrui; Cui, Yunli; Suo, Yu; Zhang, Hongli; He, Junping; Yin, Zhihong; Ning, Hongmei
Abstract: Bisphenol A (BPA), an endocrine-disrupting chemical that is largely produced and used in the plastics industry, causes environmental pollution and is absorbed by humans through consumption of food and liquids in polycarbonate containers. BPA exerts developmental and genetic toxicities to embryos and offsprings, but the embryotoxicity mechanism of this chemical is unclear. This study aimed to explore the toxic effect of BPA on embryonic development and elucidate its toxicity mechanism. Embryos of Xenopus laevis as a model were treated with different concentrations (0.1, 1, 10, and 20 μM) of BPA at the two-cell stage to investigate the developmental toxicity of BPA. Embryonic development and behaviors were monitored 24 h–96 h of BPA exposure. BPA concentrations greater than 1 μM exerted significant teratogenic effects on the Xenopus embryos, which showed short tail axis, miscoiled guts, and bent notochord as the main malformations. The 20 μM BPA-treated embryos were seriously damaged in all aspects and exhibited deformity, impaired behavioral ability, and tissue damage. The DNA integrity and apoptosis of the Xenopus embryos were also investigated. Exposure to BPA concentrations higher than 0.1 μM significantly induced DNA damage (p < 0.05). The 10 and 20 μM BPA-treated embryos exhibited higher levels of cleaved caspase-3 protein than the control. The ratios of bax/bcl- 2 mRNA were significantly higher in the 10 μM and 20 μM-treated embryos than the ratio in the control group. Overall, data indicated that BPA can delay the early development, induce DNA damage and apoptosis, and eventually cause multiple malformations in Xenopus embryos. Graphical abstract: Image 1 Highlights: BPA is embryotoxic and genotoxic to the developing embryos of X.laevis. BPA cause DNA damage and trigger caspase-3-mediated apoptosis in X.laevis. BPA cause multiple types of malformations in various organs.